Optimum Energy Waste Reduction for Lighting Energy Consumption in Faculty of Electrical Engineering (FKE), Universiti Teknikal Malaysia Melaka (UTeM): A Case Study - Ibrahim, Khairul Anwar; Sheng, See Zhe; Ahmad, Azhar (Journal of Engineering and Technology (JET), 2022)
Electrical energy waste may be defined as electricity consumption that does not perform any useful or productive action to the consumer. Energy waste and losses can cause higher electricity and therefore increase the cost of electric utilities. This paper presents a case study to estimate how much wastage of energy due to unnecessary lighting is occurring in the buildings under the Faculty of Electrical Engineering (FKE) in Universiti Teknikal Malaysia Melaka (UTeM). The study consists of an energy survey for all the current usage of all lighting fixtures in FKE. Then, by identifying the potential waste of energy, an operation scheduling of lighting fixtures is proposed, followed by data analysis to determine the potential energy savings and, hence, electricity cost. From the results, by reducing approximately 15% of the existing current lighting energy usage, FKE could save an estimated savings of about 275kWh per day, equivalent to RM2,574.80 monthly saving in electricity bills. Thus, this information can be used by the faculty and the university as part of the information to create more awareness in promoting energy-saving and reducing energy waste and loss and supporting the energy efficiency plan, whether at the national or international level.